Transmission System HD Radio - Kustiawan, Winda; Nisa, Khairun; Bas Praptama, Rifky; Alfirah Ritonga, Mahzura; Aulia, Tadzkiya; Syarqawi Arifin Nasution, Muhammad; Daffa Raihan, Muhammad; Mohammad Amri, Haikal (Politeknik Negeri FakFak, 2024)
Radio remains one of the most widely used mass communication media today, but the analog technology used in conventional radio has several limitations. To address these limitations, digital radio technology such as HD Radio was developed. HD Radio offers better, clearer, and more interference-resistant sound quality compared to analog radio. This article discusses the basic concepts, recent developments, and practical implications of the HD Radio Transmission System in the context of the modern media industry. With advanced digital technology, HD Radio is capable of delivering superior audio quality and a more immersive listening experience, as well as presenting new opportunities for broadcasters and content producers to compete in an increasingly competitive market. This study employs library research and purposive sampling methods to gather data from various literatures, journals, and interviews with selected informants.